Azidiol comprimido como conservante do leite cru destinado a contagem bacteriana por citometria de fluxo. - Joana Ferrez de Castro (2007)
The objective of the present work was to compare preservative bacteriostatic azidiol in the liquid and compressed forms, sterilized or not for gamma radiation or ethylene oxide, in the preservation of raw milk for the analysis of microbial counting by flow citometry (Bactocount IBC 150®, Bentley Inc.). The results were automatically converted through a curve of lineal regression calibrated of Individual Bacteria Count for Unit Colony Former. They were in the total 76 samples of raw milk (40ml each) by trucks isothermal tanks, of a dairy industry in Belo Horizonte, Minas Gerais, collected in the period of July by August of 2006. The unpublished use of azidiol in the form of sterilized compressed (for gamma radiation 10, 15 and 20 kGy and ethylene oxide) was evaluated front to the traditional use of liquid azidiol. The adopted delineation was in subdivided bits, having been accomplished the variance analysis and the averages comparison using itself Duncan's Test. It was concluded that the treatments did not present any statistical difference (p>0,05) regarding the microbial counting by flow citometry (Bactocount IBC 150®, Bentley Inc.). Thus azidiol liquid can be substituted by the tablet, being more indicated the utilization of the tablet to the 10 kGy to assure for harmless and not exposing the tablet the radiation high doses. The tablet sterilization for ethylene oxide also is viable.